Low plasma melatonin levels negatively correlate with melasma severity - Praharsini, I Gusti Ayu Agung; Khathreen, Corry; Suryawati, Nyoman; Indira, I Gusti Ayu Agung Elis; Pramita, I Gusti Ayu Sattwika (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Chronic exposure to ultraviolet light plays a role in the pathogenesis of melasma. Exposure to excessive sunlight leads to the formation of free radicals. As a result, the body responds by forming antioxidants such as melatonin, which is activated through the melatoninergic antioxidative system to fight oxidative stress. The relationship between melatonin and melasma is yet to be elucidated. This study aims to determine the correlation between melatonin and the severity of melasma. Methods: This analytical cross-sectional study involved 50 melasma subjects and 10 non-melasma subjects who met the inclusion criteria and were aged between 21-50 years at Prof. I.G.N.G. Ngoerah National General Hospital, Denpasar. The severity of melasma was measured by calculating the melasma area severity index (MASI) score and plasma melatonin levels were assessed using the ELISA method. Results: The median plasma melatonin level in the melasma subjects was lower (92.48 ng/ml) than in non-melasma subjects (436.35 ng/ml), with a p-value of Conclusion: Low plasma melatonin levels negatively-correlate with the severity of melasma.